COMBINED SIMULATION-ANALYTICAL MODEL OF AERODROME AIRSPACE CAPACITY - V. L. Kuznetsov; A. I. Gorchakov (Научный вестник МГТУ ГА, 2016)
An approach to the problem of estimating an aerodrome airspace capacity based on the idea of airspace «quantization» and transition to discrete time while imposing restrictions on the filling of quantum states by aircrafts has been developed in this paper. It is shown that such a formalism can significantly reduce the complexity of aircrafts movement simulation in the airfield zone, to take into account the restrictions imposed on the aerodrome airspace capacity by intersections of arrival and departure routes. The paper presents the results of the simulation experiment, illustrating the dependence of the aerodrome airspace capacity upon the number of aircraft routes intersections, v.kuznetsov@mstuca.aero.